PENGARUH KOMBINASI EKSTRAK PETROLEUM ETER BAWANG PUTIH (Allium sativum Linn) DENGAN VITAMIN C TERHADAP AKTIVITAS Candida albicans - Nurul Khaira; Misrahanum Misrahanum; Rinaldi Idroes; Muhammad Bahi; Khairan Khairan (Jurnal Natural, 2016)
Garlic (Allium sativum) contains organosulfur compound that plays an important role as an antibacterial and antifungal activities. Ascorbic acid or vitamine C also has been show has a good activity as an antioxidant and as an antifungal. The aims of the research is to determine the effect of the combination of petroleum ether garlic extract with vitamin C against Candida albicans. Zone of inhibition testing done by Kirby-Bauer method. The results showed that the combination of petroleum ether garlic extract with vitamin C in concentration of 50% did not show an activity significantly. Meanwhile, the activity of petroleum ether garlic extract alone at concentration of 50 and 75% showed activities towards Candida albicans with a diameter of inhibition zone are 19.46 and 27.46 mm respectively.